Effect of Predictive Cuing on Response Inhibition in Children with Heavy Prenatal Alcohol Exposure. (24th October 2012) - O'Brien, Jessica W.; Norman, Andria L.; Fryer, Susanna L.; Tapert, Susan F.; Paulus, Martin P.; Jones, Kenneth Lyons; Riley, Edward P.; Mattson, Sarah N.
<x xml:space="preserve">Abstract</x> Background Heavy prenatal exposure to alcohol leads to widespread cognitive deficits, including problems with attention and response inhibition. This study examined blood oxygen level‐dependent response in children with and without histories of heavy prenatal alcohol exposure during a task of response inhibition consisting of cued and noncued trials. Methods Children and adolescents (ages 8 to 18 years) with (alcohol‐exposed [AE] = 20) and without (control [CON] = 15) histories of heavy prenatal exposure to alcohol underwent functional magnetic resonance imaging while performing a go/no‐go task. Unbeknownst to subjects, a predictive cue preceded the no‐go stimulus in 87% of trials. Results Groups were matched on demographic variables and did not differ on most measures of task performance. However, following cued stimuli, the AE group demonstrated a lower hit rate to go stimuli and more conservative response bias than the CON group. AE participants demonstrated more activation during no‐go trials (inhibition) relative to go trials in the left precuneus, cingulate gyrus, anterior cingulate, and right medial frontal gyrus. During cue‐dependent response inhibition, the AE group demonstrated less activation in the left precentral and postcentral gyrus compared to the CON group. Conclusions Consistent with previous studies of response inhibition, the AE group demonstrated greater frontal and parietal activation when attempting to inhibit prepotent responses than the CON group, despite similar rates of commission errors. This study further demonstrated that the AE group had impaired behavioral performance on cued trials and demonstrated less activation in precentral and postcentral gyri relative to the CON group on these trials. This investigation provides evidence of impaired behavioral and neural processing of sequential information in fetal alcohol spectrum disorders, which can help improve inhibition in typical populations.